GERAKAN AYO SEKOLAH DI KABUPATEN BOJONEGORO: PENINGKATAN SUMBER DAYA MANUSIA MELALUI PENDIDIKAN UNTUK MENYONGSONG BONUS DEMOGRAFI - Sonyaruri Satiti (Research Centre for Population, Indonesian Institute of Sciences, 2019)
Improving the quality of human resources through education is one of the ways to benefit from the window of opportunity. The Government of Indonesia and many local governments have been conducting programs to provide easier access to education to prevent dropouts. The Local Government of Bojonegoro has been implementing a program called